The cost of Desflurane in minimal flow anaesthesia versus medium flow anaesthesia / Christopher Ting Kah Ming - Christopher Ting, Kah Ming (2018)
This was a prospective pilot study conducted at University Malaya Medical Centre (UMMC) in which 10 patients were recruited to undergo minimal flow anaesthesia and another 10 underwent medium flow anaesthesia. This study was conducted using a standardized general anesthesia delivery machine which is the Maquet FLOW-i anesthesia delivery system. Study population included subjects aged between 18 to 75 years old with American Society Of Anaesthesiologists (ASA) I to II status planned for elective surgery under general anaesthesia (with or without paralysis) with anaesthesia time more than 1 hour. The results showed mean volume of Desflurane used for minimum flow anaesthesia was 47.5 mL/hour which translates to RM 116.90/hour whereas the mean volume of Desflurane used for medium flow anaesthesia was 72.5 mL/hour which translates to RM 178.40/hour. Independent t test was applied showing no statistical significance in the difference of the mean volume and cost of Desflurane used per hour between minimum flow anaesthesia and medium flow anaesthesia. (p value = 0.140)